2019
DOI: 10.1177/1756287219875578
|View full text |Cite
|
Sign up to set email alerts
|

Age-related schwannomatosis with potential exosome-mediated contribution to prostate hyperplasia: a case report and mini-review

Abstract: A 72-year-old Caucasian man incurring a prostate hypertrophy presented with a right forearm nodule, the growth of which appeared to parallel the rise in his blood prostate-specific antigen (PSA) level. Echographic examination was consistent with a median-nerve schwannoma, and was confirmed upon magnetic resonance imaging (MRI). Excision of the nodule was readily performed without significant neural damage, and its schwannoma nature was confirmed upon immunohistochemistry analysis. Importantly, blood PSA droppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…SDEVs from high glucose-stimulated SCs have been reported to involve in mediating the development of diabetic peripheral neuropathy in a diabetic mouse model ( Jia et al, 2018 ). SDEVs are also reported to be involved in the development of age-related schwannomatosis (a rare genetic disorder that results in tumors that grow on the peripheral nerves throughout the body) ( Chignon-Sicard et al, 2019 ). These compelling findings elucidate the importance of SDEVs in glia-neuron cross talk both in health and in pathological conditions.…”
Section: Various Kinds Of Extracellular Vesicles In Glia-neuron Intra...mentioning
confidence: 99%
“…SDEVs from high glucose-stimulated SCs have been reported to involve in mediating the development of diabetic peripheral neuropathy in a diabetic mouse model ( Jia et al, 2018 ). SDEVs are also reported to be involved in the development of age-related schwannomatosis (a rare genetic disorder that results in tumors that grow on the peripheral nerves throughout the body) ( Chignon-Sicard et al, 2019 ). These compelling findings elucidate the importance of SDEVs in glia-neuron cross talk both in health and in pathological conditions.…”
Section: Various Kinds Of Extracellular Vesicles In Glia-neuron Intra...mentioning
confidence: 99%
“…Apart from peripheral neuropathy, the involvement of SC-derived exosomes in schwannomatosis has also been reported (Chignon-Sicard et al, 2019). A case study of schwannomatosis displayed two important unusual characteristics: a potential stimulating effect on prostate-specific antigen secretion and a potential growth-stimulation effect on a cognate schwannoma tumor when a large schwannoma tumor was resected (Chignon-Sicard et al, 2019). It was reasoned that the interactions between distant cells through blood and other bodily fluids could contribute to both of the unusual features above (Chignon-Sicard et al, 2019).…”
Section: The Pathologic Role Of Dysfunctional Schwann Cell-derived Ex...mentioning
confidence: 99%
“…A case study of schwannomatosis displayed two important unusual characteristics: a potential stimulating effect on prostate‐specific antigen secretion and a potential growth‐stimulation effect on a cognate schwannoma tumor when a large schwannoma tumor was resected (Chignon‐Sicard et al, 2019). It was reasoned that the interactions between distant cells through blood and other bodily fluids could contribute to both of the unusual features above (Chignon‐Sicard et al, 2019). Since exosomes are well‐known as the intercellular mediators found in most body fluids, it was suggested that exosome‐mediated cell communications were responsible for this case because the schwannoma tumor cells and tumor‐adjacent resident SCs could secrete exosomes targeting at prostate cells and distant schwannoma cells, resulting in an unexpected potential stimulating effect that led to prostate hyperplasia and cognate schwannoma (Chignon‐Sicard et al, 2019).…”
Section: The Pathologic Role Of Dysfunctional Schwann Cell‐derived Ex...mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, apart from different neuropathies, the potential contribution of SC-derived exosomes in carcinogenesis has also been suggested ( Wong et al, 2022 ). A case study of schwannomatosis revealed a promoting effect on prostate-specific antigen secretion and a growth-accelerating outcome on a cognate schwannoma after resection of a prominent schwannoma ( Chignon-Sicard et al, 2019 ). This was explained by exosomes secreted from schwannoma cells and tumor-adjacent resident SCs that targeted prostate cells and distant schwannoma cells.…”
Section: Introductionmentioning
confidence: 99%